Light and electron microscopic investigations of nasopharyngeal carcinomas with regard to the viral etiology of these tumors - Arnold, W. (J Cancer Res Clin Oncol, 1979)
Five carcinomata of the nasopharynx (four lymphoepithelial carcinomata of the Regaud type and one squamous cell carcinoma) were examined light and electron microscopically. In addition to the familiar histological and cytological features of these tumors, and because of an increased antibody titer against Epstein-Barr virus in all five patients, all those cytoplasmic and nuclear inclusions were examined which could be interpreted as indicative of a virus contact. The following structures were found: 1. Particles and microtubules which correspond in diameter, shape, and location to Corona viruses. 2. Particles surrounded by a double membrane and resembling in form and diameter Oncorna viruses. 3. Tubulo-reticular, coil-shaped cytoplasmic inclusions interpreted as an unspecific reaction of the host cell to viral attack. 4. Spherical nuclear bodies, which are frequently observed in tumors and in viral infections. 5. Intranuclear particles which correspond in diameter, structure, and distribution to viruses of the herpes type such as have been described in cell cultures of Burkitt lymphoma and nasopharyngeal carcinoma. The fifth group particularly was discussed in detail with regard to differentiation between those particles and other structures which could simulate a virus structure. Together with the appearance of increased ribosomes and of particular chromatin distribution within the tumor cell nuclei, the particles we discussed have been interpreted as morphological indications of a virus etiology of the examined tumors.